Peningkatan Kesadaran Gizi melalui Community Feeding Center (CFC) untuk Mengurangi Stunting di Dusun Srunggo 2, Kalurahan Selopamioro, Kapanewon Imogiri, Kabupaten Bantul - Pratama, Arif Setya; Agusetianto, Adrian Dwi; Rasyida, Sabrina Rizka; Triputra, Muhammad Dhafa; Agustiani, Anitta Dwi; Putri, Mela Adelia; Fadhilah, Resi Malik; Tantri, Haliza Tiara; Mubarak, Sultan Zein; Juniarti, Rizky; Fridayani, Helen Dian (Universitas Muhammadiyah Yogyakarta, 2025)
Stunting, a long-term nutritional condition that has an impact on children's growth, is characterized by a height that is lower than age standards due to ongoing nutritional deficiencies. In Srunggo 2 Hamlet, Selopamioro Village, Kapanewon Imogiri, Bantul Regency, this problem still occurs a lot. This is caused by the high rate of early marriage, lack of understanding and nutritional literacy among mothers and young women, and lack of public awareness of the importance of balanced nutrition. Through the Community Feeding Center (CFC) program, this community effort aims to increase nutritional awareness and increase access to healthy food. This program teaches the importance of balanced nutrition, assistance to pregnant women and toddlers, and good nutrition for children's growth. Apart from that, information about stunting, healthy eating patterns, and the importance of consuming blood supplement tablets for pregnant women and young women to prevent anemia, one of the risk factors for stunting in children, has been disseminated. The results of the activity show that the community better understands the importance of balanced nutrition, as shown by increased participation in education and changes to healthier eating patterns. Apart from that, pregnant women and young women are more aware of consuming blood supplement tablets regularly. It is hoped that with the existence of the Community Feeding Center and this educational program, community behavior will change in terms of parenting patterns and fulfilling children's nutrition. Thus, in the long term, the stunting rate in Srunggo 2 Hamlet can be reduced significantly.